Electrolyte, preparation method thereof and lithium ion battery

By using nanoparticle lithium-containing compounds in the lithium-ion battery electrolyte, the problem of poor stability of SEI film in lithium-ion batteries is solved, and a more stable and uniform SEI film formation is achieved, reducing the internal resistance of the battery and gas generation, and improving the battery performance.

CN119764563APending Publication Date: 2025-04-04BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411856311.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The stability of the solid electrolyte interface (SEI) in lithium-ion batteries is poor, resulting in increased gas production and internal resistance of the battery, affecting performance.

Method used

The lithium-containing compound in the form of nanoparticles is used as the component of the electrolyte, and the composition and structure of the SEI film are optimized through small size effects and high specific surface area, reducing the desolvation energy barrier of lithium ions, and promoting the uniform and stable formation of the SEI film.

Benefits of technology

Form a SEI film with good stability, reduce decomposition and reformation, reduce gas generation and internal resistance, and improve the performance of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764563A_ABST
    Figure CN119764563A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte, a preparation method thereof and a lithium ion battery, relates to the technical field of lithium ion batteries, and aims to solve the problem of poor stability of a solid electrolyte interface (SEI) in the lithium ion battery. The electrolyte comprises an electrolyte salt, a solvent and a nano-granular lithium-containing compound dispersed in the solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to an electrolyte and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] In lithium-ion batteries, the stability of the solid electrolyte interface (SEI) has a great impact on the life, power, fast charging and other performance of lithium batteries. Among them, the electrolyte is the key factor affecting the stability of the SEI film. When the stability of the SEI film is poor, the process of decomposition and re-formation will occur, resulting in the gas production of lithium-ion batteries, and it will also increase the internal resistance of lithium-ion batteries and hinder the conduction of lithium ions. Summary of the invention

[0003] The purpose of the present application is to provide an electrolyte and a preparation method thereof, and a lithium-ion battery, aiming to solve the problem of poor stability of the solid electrolyte interface (SEI) in lithium-ion batteries.

[0004] In order to achieve the above objectives, this application adopts the following technical solutions:

[0005] In a first aspect, the present application provides an electrolyte solution, which includes an electrolyte salt, a solvent, and a lithium-containing compound in the form of nanoparticles dispersed in the solvent.

[0006] In the electrolyte provided in the embodiments of the present application, the lithium-containing compound in the form of nanoparticles can more easily participate in the formation process of the SEI film due to its small size effect and high specific surface area, optimize its composition and structure, and help form a SEI film with better lithium conductivity and stability.

[0007] Moreover, the addition of lithium-containing compounds in the form of nanoparticles will change the arrangement and interaction of solvent molecules in the electrolyte, thereby affecting the solvation state of lithium ions, helping to reduce the energy barrier for lithium ion desolvation, making it easier for lithium ions to be freed from solvent molecules, and providing more sufficient lithium ions during the formation of the SEI film, thereby promoting the uniform and stable formation of the SEI film.

[0008] In addition, lithium-containing compounds in nanoparticle form can optimize the composition and structure of the electrolyte and reduce unnecessary ion consumption. For example, by adsorbing harmful substances in the electrolyte (such as hydrofluoric acid) to maintain the stability of the electrolyte, thereby indirectly reducing the consumption of lithium ions, helping to uniform the lithium ion conduction rate in the electrolyte, making the formed SEI film more uniform, and further improving the stability of the SEI film.

[0009] Therefore, a lithium-containing compound in nanoparticle form can form a SEI film with better stability, reduce the decomposition and reformation of the SEI film, thereby reducing the gas generated by decomposition and reformation, and reducing the internal resistance of the lithium-ion battery, thereby improving the performance of the lithium-ion battery.

[0010] In some embodiments, the lithium-containing compound includes at least one of lithium oxide, lithium carbonate, lithium nitride, lithium phosphide, lithium fluoride, lithium nitrate, and lithium iodide.

[0011] In some embodiments, the lithium-containing compound includes at least three of lithium oxide, lithium carbonate, lithium nitride, lithium phosphide, lithium fluoride, lithium nitrate, and lithium iodide.

[0012] In some embodiments, the average particle size of the lithium-containing compound is in the range of 10 nm to 500 nm.

[0013] In some embodiments, the ratio of the mass of each lithium-containing compound to the mass of the electrolyte is in the range of 0.001 to 0.05.

[0014] In some embodiments, the electrolyte further comprises: 5-isosorbide mononitrate.

[0015] In some embodiments, the ratio of the mass of 5-isosorbide mononitrate to the mass of the electrolyte is in the range of 0.001 to 0.05.

[0016] In some embodiments, the electrolyte further includes at least one of magnesium oxide in nanoparticle form and aluminum oxide in nanoparticle form.

[0017] In some embodiments, the average particle size of magnesium oxide is in the range of 10 nm to 500 nm.

[0018] In some embodiments, the average particle size of aluminum oxide is in the range of 10 nm to 500 nm.

[0019] In some embodiments, the ratio of the mass of magnesium oxide to the mass of the electrolyte is in the range of 0.001 to 0.05.

[0020] In some embodiments, the ratio of the mass of aluminum oxide to the mass of the electrolyte is in the range of 0.001 to 0.05.

[0021] In some embodiments, the electrolyte further includes: a dispersant.

[0022] In some embodiments, the dispersant includes: cetyltrimethylammonium bromide.

[0023] In some embodiments, the ratio of the mass of the dispersant to the mass of the electrolyte is in the range of 0.005 to 0.05.

[0024] In some embodiments, the electrolyte salt includes at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.

[0025] In some embodiments, the solvent includes at least one of an ether solvent and an ester solvent.

[0026] In a second aspect, the present application provides a method for preparing an electrolyte. The method for preparing the electrolyte comprises:

[0027] calcining the lithium-containing compound;

[0028] The calcined lithium-containing compound is mixed with an electrolyte salt and a solvent; wherein the lithium-containing compound is in a nanoparticle form.

[0029] It can be understood that the present application provides a method for preparing an electrolyte, and the beneficial effects achieved by the method can be referred to the beneficial effects of the electrolyte described above, which will not be repeated here.

[0030] In some embodiments, the calcination temperature ranges from 300°C to 500°C.

[0031] In a third aspect, the present application provides a lithium-ion battery, which includes: a positive electrode, a negative electrode, and an electrolyte as described in any one of the above embodiments located between the positive electrode and the negative electrode.

[0032] It can be understood that the present application provides a lithium-ion battery, and the beneficial effects achieved by the battery can be referred to the beneficial effects of the electrolyte described above, which will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0034] Figure 1 A flow chart of a method for preparing an electrolyte is provided for an embodiment of the present application. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0036] In the description of this application, it should be understood that the terms "upper", "lower", "left", "right", "front", "back", "inside", "outside", etc. indicate directions or positional relationships based on the directions or relative positional relationships shown in the accompanying drawings, and are only for the convenience of describing this application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on this application. Unless otherwise specified, the above-mentioned directional description can be flexibly set in the process of actual application under the condition that the relative positional relationship shown in the accompanying drawings is met.

[0037] In the description of the present application, unless otherwise specified, “plurality” means two or more.

[0038] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0039] In the present application, the terms "comprises", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, article or device. In the absence of further restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, article or device including the element.

[0040] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.

[0041] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0042] As a representative of modern high-performance batteries, lithium-ion batteries have the advantages of high energy density, long life, and environmental protection, and are widely used in various fields.

[0043] The present application provides a lithium ion battery, which comprises a positive electrode, a negative electrode and an electrolyte located between the positive electrode and the negative electrode.

[0044] The positive electrode is the polarity in the battery that is responsible for storing positive charges. The positive electrode material can embed and release lithium ions, and the storage and release of lithium ions are achieved through the chemical reaction of the positive electrode material. During the discharge process, lithium ions are de-embedded from the positive electrode material and transferred to the negative electrode material through the electrolyte, completing the discharge process of the battery.

[0045] The negative electrode is the polarity in the battery that is responsible for storing negative charges. The negative electrode material is able to release lithium ions and store lithium ions during the charging process. When the lithium-ion battery is charged, the negative electrode absorbs externally provided lithium ions and participates in electrochemical reactions, thereby storing electrical energy.

[0046] The electrolyte is the ion transport medium in lithium-ion batteries, located between the positive and negative electrodes, allowing lithium ions to move freely between the positive and negative electrodes of the battery. During the charging process, lithium ions are released from the positive electrode, migrate to the negative electrode in the electrolyte and embed into the negative electrode material; during the discharge process, it is the reverse process.

[0047] Electrolytes are ion carriers in batteries, usually salts composed of cations and anions. Cations are usually metal ions such as lithium, sodium, copper, and iron, while anions can be fluorides, phosphates, sulfates, etc. Solvents are carriers of electrolytes, usually organic solvents or water.

[0048] In some embodiments, the electrolyte salt includes at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.

[0049] In some embodiments, the solvent includes at least one of an ether solvent and an ester solvent.

[0050] The composition and concentration of the electrolyte directly affect the electrochemical properties of the battery, including voltage, capacity and cycle life.

[0051] The solid electrolyte interface (SEI) membrane is a passivation layer covering the surface of the electrode material formed by the reaction between the electrode material and the electrolyte at the solid-liquid interface during the first charge and discharge process of the lithium-ion battery. The passivation layer has the characteristics of a solid electrolyte and is an insulator of electrons, but it is a Li + Excellent conductor.

[0052] The stability of the solid electrolyte interface (SEI) has a great impact on the life, power, fast charging and other performance of lithium batteries. Among them, the electrolyte is the key factor affecting the stability of the SEI film. When the stability of the SEI film is poor, the process of decomposition and re-formation will occur, resulting in the gas production of lithium-ion batteries, and it will also increase the internal resistance of lithium-ion batteries and hinder the conduction of lithium ions.

[0053] Based on this, an embodiment of the present application provides an electrolyte solution. The electrolyte solution includes: an electrolyte salt, a solvent, and a lithium-containing compound in the form of nanoparticles dispersed in the solvent.

[0054] As mentioned above, the electrolyte salt is the source of lithium ions, and the solvent can dilute the electrolyte in the electrolyte and regulate the concentration of the electrolyte.

[0055] Nanoparticle-shaped lithium-containing compounds can more easily participate in the formation of the SEI film due to their small size effect and high specific surface area, optimize their composition and structure, and help form a SEI film with better lithium conductivity and stability.

[0056] Moreover, the addition of lithium-containing compounds in the form of nanoparticles will change the arrangement and interaction of solvent molecules in the electrolyte, thereby affecting the solvation state of lithium ions, helping to reduce the energy barrier for lithium ion desolvation, making it easier for lithium ions to be freed from solvent molecules, and providing more sufficient lithium ions during the formation of the SEI film, thereby promoting the uniform and stable formation of the SEI film.

[0057] In addition, lithium-containing compounds in nanoparticle form can optimize the composition and structure of the electrolyte and reduce unnecessary ion consumption. For example, by adsorbing harmful substances in the electrolyte (such as hydrofluoric acid) to maintain the stability of the electrolyte, thereby indirectly reducing the consumption of lithium ions, helping to uniform the lithium ion conduction rate in the electrolyte, making the formed SEI film more uniform, and further improving the stability of the SEI film.

[0058] Therefore, a lithium-containing compound in nanoparticle form can form a SEI film with better stability, reduce the decomposition and reformation of the SEI film, thereby reducing the gas generated by decomposition and reformation, and reducing the internal resistance of the lithium-ion battery, thereby improving the performance of the lithium-ion battery.

[0059] In some embodiments, the lithium-containing compound includes at least one of lithium oxide, lithium carbonate, lithium nitride, lithium phosphide, lithium fluoride, lithium nitrate, and lithium iodide.

[0060] It is understandable that lithium oxide (Li 2 O) and lithium carbonate (Li 2 CO 3 ) can serve as an inorganic component of the SEI film, forming a dense SEI film structure and providing a stable lithium ion transmission channel.

[0061] Lithium Nitride (Li 3 N) can significantly improve the ion conduction efficiency and stability of the SEI film, help to form an interfacial film with fast ion conduction capability, and thus improve the deposition uniformity of metallic lithium.

[0062] Lithium fluoride (LiF) has the characteristics of high mechanical strength, low solubility and wide band gap. LiF-rich SEI film can inhibit electrolyte decomposition and improve ion transport performance.

[0063] Lithium nitrate (LiNO 3 ) can form a stable interface film with fast ion conduction capability on the surface of metallic lithium, thereby helping the uniform deposition of metallic lithium, reducing the growth of metallic lithium dendrites, and improving the stability of the metallic lithium interface.

[0064] Lithium iodide (LiI) can improve the conductivity and stability of SEI film during the formation of SEI film.

[0065] Therefore, at least one of the above lithium-containing compounds can construct a SEI film with better lithium conductivity in the electrolyte.

[0066] In some embodiments, the lithium-containing compound includes at least three of lithium oxide, lithium carbonate, lithium nitride, lithium phosphide, lithium fluoride, lithium nitrate, and lithium iodide.

[0067] It can be understood that the lithium-containing compounds include: at least three of lithium oxide, lithium carbonate, lithium nitride, lithium phosphide, lithium fluoride, lithium nitrate and lithium iodide in the electrolyte, which can increase the entropy of the electrolyte, produce higher configuration entropy, increase the disorder of the electrolyte microstructure, reduce the size of the ion clusters, and make the ion clusters have higher diffusion rate and better transmission performance; at the same time, the introduction of a variety of lithium-containing compounds also increases the types and number of solvation structures, making the solvation structures more diversified, reducing the solvation strength between lithium ions and solvents, thereby increasing the degree of freedom of the system, and the diversified solvation structures help to reduce the fluid dynamics radius, further improve the transport kinetics of ions, reduce the interaction and hindrance between ions, and make the ion distribution in the electrolyte more uniform, which is beneficial to Li + The rapid transport of lithium ions promotes the diffusion of lithium ions and the formation of a stable SEI film.

[0068] In some embodiments, the average particle size of the lithium-containing compound is in the range of 10 nm to 500 nm.

[0069] For example, the average particle size of the lithium-containing compound may be 10 nm, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm, etc., which is not limited herein.

[0070] It can be understood that the above-mentioned setting can make the lithium-containing compound have a better size effect. Nano-sized lithium compounds can form a stable protective film on the surface due to their large surface area and high surface energy, thereby preventing the absorption of moisture; and the lithium-containing compounds within the above-mentioned average particle size range are more likely to form a stable structure in the battery material, thereby preventing the decomposition of lithium salts, thereby reducing the generation of hydrofluoric acid, thereby reducing the corrosion of the SEI film, and is conducive to the formation of a SEI film with better stability.

[0071] In some embodiments, the ratio of the mass of each lithium-containing compound to the mass of the electrolyte is in the range of 0.001 to 0.05.

[0072] Illustratively, the ratio of the mass of each lithium-containing compound to the mass of the electrolyte may be 0.001, 0.01, 0.02, 0.03, 0.04 or 0.05, etc., which is not limited here.

[0073] It can be understood that the above configuration can keep the ion concentration in the electrolyte within a suitable range, which is helpful for forming a stable SEI film.

[0074] In some embodiments, the electrolyte further comprises: 5-isosorbide mononitrate.

[0075] 5-isosorbide mononitrate can generate LiN x O y , where 0<x<0.33, 0.5<y<1, improves the uniformity of Li deposition and forms a more stable and uniform SEI film.

[0076] In some embodiments, the ratio of the mass of 5-isosorbide mononitrate to the mass of the electrolyte is in the range of 0.001 to 0.05.

[0077] For example, the ratio of the mass of 5-isosorbide mononitrate to the mass of the electrolyte can be 0.001, 0.01, 0.02, 0.03, 0.04 or 0.05, etc., which is not limited here.

[0078] Through the above settings, the LiN generated in the electrolyte can be x O y Within an appropriate range, the stability and uniformity of the SEI film are further improved.

[0079] In some embodiments, the electrolyte further includes at least one of magnesium oxide in nanoparticle form and aluminum oxide in nanoparticle form.

[0080] It can be understood that nanoparticles of magnesium oxide (MgO) can react with water molecules to help remove water from lithium-containing compounds and solvents, while nanoparticles of aluminum oxide (Al 2 O3 ) can react with HF in the electrolyte to generate HF; and MgO and Al 2 O 3 Nanoparticles can slow down the Li 2 O hydrolysis rate, increasing Li 2 O utilization, thereby stabilizing the electrolyte composition, slowing down corrosion, and reducing the loss of electrode materials in subsequent cycles, thereby reducing the gas production of lithium-ion batteries and reducing the internal resistance of lithium-ion batteries.

[0081] In some embodiments, the average particle size of magnesium oxide is in the range of 10 nm to 500 nm.

[0082] For example, the average particle size of magnesium oxide may be 10 nm, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm, etc., which is not limited here.

[0083] In some embodiments, the average particle size of aluminum oxide is in the range of 10 nm to 500 nm.

[0084] For example, the average particle size of aluminum oxide may be 10 nm, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm, etc., which is not limited here.

[0085] The above-mentioned setting of the average particle diameters of magnesium oxide and aluminum oxide within the range of 10 nm to 500 nm can increase the contact area between magnesium oxide and the lithium-containing compound in the electrolyte and the water in the solvent, and between aluminum oxide and HF in the electrolyte, and can further remove the water in the lithium-containing compound in the electrolyte and the solvent, and the HF in the electrolyte.

[0086] In some embodiments, the ratio of the mass of magnesium oxide to the mass of the electrolyte is in the range of 0.001 to 0.05.

[0087] For example, the ratio of the mass of magnesium oxide to the mass of the electrolyte may be 0.001, 0.01, 0.02, 0.03, 0.04 or 0.05, etc., which is not limited here.

[0088] In some embodiments, the ratio of the mass of aluminum oxide to the mass of the electrolyte is in the range of 0.001 to 0.05.

[0089] For example, the ratio of the mass of aluminum oxide to the mass of the electrolyte may be 0.001, 0.01, 0.02, 0.03, 0.04 or 0.05, etc., which is not limited here.

[0090] The ratio of the mass of magnesium oxide to the mass of the electrolyte and the ratio of the mass of aluminum oxide to the mass of the electrolyte are both set within the range of 0.001 to 0.05, which can fully exert the role of magnesium oxide and aluminum oxide in removing the lithium-containing compounds in the electrolyte, moisture in the solvent and HF in the electrolyte, thereby improving the performance of the lithium-ion battery.

[0091] In some embodiments, the electrolyte further includes: a dispersant.

[0092] It is understandable that the dispersant can be adsorbed on the surface of the nanoparticles to form an adsorption layer, thereby preventing the particles from agglomerating. At the same time, the dispersant can also increase the distance between the particles to prevent the agglomeration of the nanoparticles. The dispersant helps the lithium-containing compound in the form of nanoparticles, the aluminum oxide in the form of nanoparticles, and the magnesium oxide in the form of nanoparticles to be more evenly dispersed in the electrolyte, thereby reducing the internal resistance of the lithium-ion battery and improving the performance of the lithium-ion battery.

[0093] In some embodiments, the dispersant includes: cetyltrimethylammonium bromide.

[0094] Hexadecyltrimethylammonium bromide (CTAB) is both hydrophilic and hydrophobic, which helps to evenly disperse the nanoparticles in the electrolyte and reduce the agglomeration of the particles. CTAB can form a protective layer on the surface of the nanoparticles to prevent direct contact between the particles, effectively reduce the agglomeration phenomenon, and thus enhance the stability of the particles.

[0095] In some embodiments, the ratio of the mass of the dispersant to the mass of the electrolyte is in the range of 0.005 to 0.05.

[0096] For example, the ratio of the mass of the dispersant to the mass of the electrolyte may be 0.005, 0.01, 0.02, 0.03, 0.04 or 0.05, etc., which is not limited here.

[0097] Setting the ratio of the mass of the above-mentioned dispersant to the mass of the electrolyte in the range of 0.001 to 0.05 can better disperse the nano-particulate lithium-containing compound, nano-particulate aluminum oxide and nano-particulate magnesium oxide in the electrolyte, thereby further improving the performance of the lithium-ion battery.

[0098] The embodiments of the present application provide a method for preparing an electrolyte. Figure 1 As shown, the preparation method of the electrolyte includes: S1-S2.

[0099] S1: calcining the lithium-containing compound.

[0100] S2: mixing the calcined lithium-containing compound with an electrolyte salt and a solvent, wherein the lithium-containing compound is in a nanoparticle form.

[0101] It can be understood that the water content of the lithium-containing compound can be removed after calcining to reduce its influence on the electrolyte, and then the lithium-containing compound without water content is mixed evenly with the electrolyte salt and the solvent to obtain the electrolyte.

[0102] Here, the lithium-containing compound particles obtained after calcination may cause agglomeration problems, and may be sieved before use, with a sieve size of, for example, 100-600 meshes.

[0103] In some embodiments, the calcination temperature ranges from 300°C to 500°C.

[0104] For example, the calcination temperature may be 300° C., 350° C., 400° C., 450° C., or 500° C., etc., but is not limited thereto.

[0105] The present application is described in further detail below by taking several specific experiments as examples.

[0106] Example 1

[0107] Embodiment 1 provides an electrolyte, the electrolyte comprising:

[0108] The electrolyte was 1 M lithium hexafluorophosphate.

[0109] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0110] and, 1% lithium oxide, 1% lithium carbonate, 1% lithium phosphide, 1% magnesium oxide, 1% aluminum oxide, 1% isosorbide 5-mononitrate and 1.5% hexadecyltrimethylammonium bromide.

[0111] Among them, lithium oxide, lithium carbonate, lithium phosphide, magnesium oxide and aluminum oxide are all particles with a median particle size of 300 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 1% lithium oxide means that the mass ratio of lithium oxide in the electrolyte is 1%, or the ratio of the mass of lithium oxide to the mass of the electrolyte is 0.01, and the percentages of other substances are described in the same way.

[0112] Example 2

[0113] Embodiment 2 provides an electrolyte, the electrolyte comprising:

[0114] The electrolyte was 1 M lithium hexafluorophosphate.

[0115] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0116] and, 1% lithium nitride, 1% lithium fluoride, 1% lithium nitrate, 1% lithium iodide, 0.5% magnesium oxide, 0.5% aluminum oxide, and 1.5% hexadecyltrimethylammonium bromide.

[0117] Among them, lithium nitride, lithium fluoride, lithium nitrate, lithium iodide, magnesium oxide and aluminum oxide are all particles with a median particle size of 300 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 1% of lithium nitride means that the mass ratio of lithium nitride in the electrolyte is 1%, or the ratio of the mass of lithium nitride to the mass of the electrolyte is 0.01, and the percentages of other substances are described in the same way.

[0118] Example 3

[0119] Embodiment 3 provides an electrolyte, the electrolyte comprising:

[0120] The electrolyte was 1 M lithium hexafluorophosphate.

[0121] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0122] and, 1% lithium oxide, 1% lithium carbonate, 1% lithium phosphide, 1% lithium nitride, 1% lithium fluoride, 1% lithium nitrate, 1% lithium iodide, 0.5% magnesium oxide, 0.5% aluminum oxide, 1% isosorbide 5-mononitrate, and 1.5% hexadecyltrimethylammonium bromide.

[0123] Among them, lithium oxide, lithium carbonate, lithium phosphide, lithium nitride, lithium fluoride, lithium nitrate, lithium iodide, magnesium oxide and aluminum oxide are all particles with a median particle size of 300 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 1% of lithium nitride means that the mass ratio of lithium nitride in the electrolyte is 1%, or the ratio of the mass of lithium nitride to the mass of the electrolyte is 0.01, and the percentages of other substances are described in the same way.

[0124] Example 4

[0125] Embodiment 4 provides an electrolyte, the electrolyte comprising:

[0126] The electrolyte was 1 M lithium hexafluorophosphate.

[0127] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0128] and, 0.1% lithium oxide, 0.1% lithium carbonate, 0.1% lithium phosphide, 0.1% magnesium oxide, 0.1% aluminum oxide, 0.1% isosorbide 5-mononitrate and 0.5% hexadecyltrimethylammonium bromide.

[0129] Among them, lithium oxide, lithium carbonate, lithium phosphide, magnesium oxide and aluminum oxide are all particles with a median particle size of 300 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 0.1% lithium nitride means that the mass ratio of lithium nitride in the electrolyte is 0.1%, or the ratio of the mass of lithium nitride to the mass of the electrolyte is 0.001, and the percentages of other substances are described in the same way.

[0130] Example 5

[0131] Embodiment 5 provides an electrolyte, the electrolyte comprising:

[0132] The electrolyte was 1 M lithium hexafluorophosphate.

[0133] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0134] and, 5% lithium oxide, 5% lithium carbonate, 5% lithium phosphide, 5% magnesium oxide, 5% aluminum oxide, 5% isosorbide 5-mononitrate, and 5% hexadecyltrimethylammonium bromide.

[0135] Among them, lithium oxide, lithium carbonate, lithium phosphide, magnesium oxide and aluminum oxide are all particles with a median particle size of 300 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 5% lithium oxide means that the mass ratio of lithium oxide in the electrolyte is 5%, or the ratio of the mass of lithium oxide to the mass of the electrolyte is 0.05, and the percentages of other substances are described in the same way.

[0136] Example 6

[0137] Embodiment 6 provides an electrolyte, the electrolyte comprising:

[0138] The electrolyte was 1 M lithium hexafluorophosphate.

[0139] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0140] and, 0.1% lithium nitride, 0.1% lithium fluoride, 0.1% lithium nitrate, 0.1% lithium iodide, 0.1% magnesium oxide, 0.1% aluminum oxide, and 0.5% hexadecyltrimethylammonium bromide.

[0141] Among them, lithium nitride, lithium fluoride, lithium nitrate, lithium iodide, magnesium oxide and aluminum oxide are all particles with a median particle size of 300 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 0.1% lithium nitride means that the mass ratio of lithium nitride in the electrolyte is 0.1%, or the ratio of the mass of lithium nitride to the mass of the electrolyte is 0.001, and the percentages of other substances are described in the same way.

[0142] Example 7

[0143] Embodiment 7 provides an electrolyte, the electrolyte comprising:

[0144] The electrolyte was 1 M lithium hexafluorophosphate.

[0145] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0146] and, 5% lithium nitride, 5% lithium fluoride, 5% lithium nitrate, 5% lithium iodide, 5% magnesium oxide, 5% aluminum oxide, and 5% hexadecyltrimethylammonium bromide.

[0147] Among them, lithium nitride, lithium fluoride, lithium nitrate, lithium iodide, magnesium oxide and aluminum oxide are all particles with a median particle size of 300 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 5% lithium nitride means that the mass ratio of lithium nitride in the electrolyte is 5%, or the ratio of the mass of lithium nitride to the mass of the electrolyte is 0.05, and the percentages of other substances are described in the same way.

[0148] Example 8

[0149] Embodiment 8 provides an electrolyte, the electrolyte comprising:

[0150] The electrolyte was 1 M lithium hexafluorophosphate.

[0151] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0152] and, 0.1% lithium oxide, 0.1% lithium carbonate, 0.1% lithium phosphide, 0.1% lithium nitride, 0.1% lithium fluoride, 0.1% lithium nitrate, 0.1% lithium iodide, 0.1% magnesium oxide, 0.1% aluminum oxide, 0.1% isosorbide 5-mononitrate, and 0.1% hexadecyltrimethylammonium bromide.

[0153] Among them, lithium oxide, lithium carbonate, lithium phosphide, lithium nitride, lithium fluoride, lithium nitrate, lithium iodide, magnesium oxide and aluminum oxide are all particles with a median particle size of 300 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 0.1% of lithium nitride means that the mass ratio of lithium nitride in the electrolyte is 0.1%, or the ratio of the mass of lithium nitride to the mass of the electrolyte is 0.001, and the percentages of other substances are described in the same way.

[0154] Example 9

[0155] Embodiment 9 provides an electrolyte, the electrolyte comprising:

[0156] The electrolyte was 1 M lithium hexafluorophosphate.

[0157] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0158] and, 5% lithium oxide, 5% lithium carbonate, 5% lithium phosphide, 5% lithium nitride, 5% lithium fluoride, 5% lithium nitrate, 5% lithium iodide, 5% magnesium oxide, 5% aluminum oxide, 5% isosorbide 5-mononitrate, and 5% hexadecyltrimethylammonium bromide.

[0159] Among them, lithium oxide, lithium carbonate, lithium phosphide, lithium nitride, lithium fluoride, lithium nitrate, lithium iodide, magnesium oxide and aluminum oxide are all particles with a median particle size of 300 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 5% lithium nitride means that the mass ratio of lithium nitride in the electrolyte is 5%, or the ratio of the mass of lithium nitride to the mass of the electrolyte is 0.05, and the percentages of other substances are described in the same way.

[0160] Example 10

[0161] Embodiment 10 provides an electrolyte, the electrolyte comprising:

[0162] The electrolyte was 1 M lithium hexafluorophosphate.

[0163] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0164] and, 1% lithium oxide, 1% lithium carbonate, 1% lithium phosphide, 1% lithium nitride, 1% lithium fluoride, 1% lithium nitrate, 1% lithium iodide, 0.5% magnesium oxide, 0.5% aluminum oxide, 1% isosorbide 5-mononitrate, and 0.5% hexadecyltrimethylammonium bromide.

[0165] Among them, lithium oxide, lithium carbonate, lithium phosphide, lithium nitride, lithium fluoride, lithium nitrate, lithium iodide, magnesium oxide and aluminum oxide are all particles with a median particle size of 300 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 1% of lithium nitride means that the mass ratio of lithium nitride in the electrolyte is 1%, or the ratio of the mass of lithium nitride to the mass of the electrolyte is 0.01, and the percentages of other substances are described in the same way.

[0166] Embodiment 11

[0167] Embodiment 11 provides an electrolyte, the electrolyte comprising:

[0168] The electrolyte was 1 M lithium hexafluorophosphate.

[0169] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0170] and, 1% lithium oxide, 1% lithium carbonate, 1% lithium phosphide, 1% lithium nitride, 1% lithium fluoride, 1% lithium nitrate, 1% lithium iodide, 0.5% magnesium oxide, 0.5% aluminum oxide, 1% isosorbide 5-mononitrate, and 0.5% hexadecyltrimethylammonium bromide.

[0171] Among them, lithium oxide, lithium carbonate, lithium phosphide, lithium nitride, lithium fluoride, lithium nitrate, lithium iodide, magnesium oxide and aluminum oxide are all particles with a median particle size of 500 nm. The percentage represents the mass ratio of the substance in the electrolyte, for example, 1% of lithium nitride means that the mass ratio of lithium nitride in the electrolyte is 1%, or the ratio of the mass of lithium nitride to the mass of the electrolyte is 0.01, and the percentages of other substances are described in the same way.

[0172] Comparative Example 1

[0173] Comparative Example 1 provides an electrolyte comprising:

[0174] The electrolyte was 1 M lithium hexafluorophosphate.

[0175] The solvent is ethylene carbonate and diethyl carbonate in a volume ratio of 1:1.

[0176] Performance Testing

[0177] (1) Preparation of small soft-pack lithium-ion batteries: lithium iron phosphate was used as the positive electrode, graphite was used as the negative electrode, Celgard 2400 polypropylene film was used as the separator, and the electrolyte was selected from the above-mentioned embodiments and comparative examples. The coating, sheet making, assembly, infiltration, formation, aging, and capacity separation processes were performed to obtain lithium-ion batteries corresponding to the electrolytes of the embodiments and comparative examples.

[0178] (2) The gas production volume of the electrolytes of the above-mentioned embodiments and comparative examples during high temperature (45°C to 65°C) aging in the lithium ion battery preparation process was collected. The results are shown in Table 1.

[0179] (3) Under the condition of 25% SOC (the proportional relationship between the current battery charge and the total capacity), the lithium-ion batteries corresponding to the electrolytes of the above embodiments and comparative examples were subjected to a charging DC internal resistance test. The specific test conditions include: charging at a rate of 3C for 10 seconds at 25 degrees to measure the DC internal resistance; charging at a rate of 1.5C for 10 seconds at 0 degrees to measure the DC internal resistance; and charging at a rate of 1C for 10 seconds at a minus 10 degrees to measure the DC internal resistance. The results are shown in Table 1.

[0180] Table 1 Gas production volume and DC internal resistance during high temperature aging in the lithium ion battery preparation process corresponding to the examples and comparative examples

[0181]

[0182]

[0183] As can be seen from Table 1, the high-temperature aging gas production and charging DC internal resistance of the lithium-ion batteries prepared by the electrolytes of Examples 1 to 11 are both lower than those of the lithium-ion batteries prepared by the electrolytes of Comparative Example 1, and have lower gas production and lower internal resistance, indicating that the lithium-ion batteries prepared by the electrolytes of Examples 1 to 11 have better performance, which may be attributed to the fact that the electrolytes of Examples 1 to 11 can form a SEI film with better stability, reduce the decomposition and reformation of the SEI film, thereby reducing the gas generated by decomposition and reformation, and reducing the internal resistance of the lithium-ion battery.

[0184] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. An electrolyte, characterized in that: include: An electrolyte salt, a solvent, and a lithium-containing compound in a nanoparticle form dispersed in the solvent.

2. The electrolyte according to claim 1, characterized in that The lithium-containing compound includes at least one of lithium oxide, lithium carbonate, lithium nitride, lithium phosphide, lithium fluoride, lithium nitrate and lithium iodide.

3. The electrolyte according to claim 2, characterized in that The lithium-containing compound includes at least three of lithium oxide, lithium carbonate, lithium nitride, lithium phosphide, lithium fluoride, lithium nitrate and lithium iodide.

4. The electrolyte according to claim 1, characterized in that The average particle size of the lithium-containing compound is in the range of 10 nm to 500 nm.

5. The electrolyte according to claim 1, characterized in that The ratio of the mass of each lithium-containing compound to the mass of the electrolyte is in the range of 0.001 to 0.

05.

6. The electrolyte according to claim 1, characterized in that The electrolyte also includes: 5-isosorbide mononitrate.

7. The electrolyte according to claim 6, characterized in that The ratio of the mass of 5-isosorbide mononitrate to the mass of the electrolyte is in the range of 0.001 to 0.

05.

8. The electrolyte according to claim 1, characterized in that The electrolyte also includes: at least one of nano-particle magnesium oxide and nano-particle aluminum oxide.

9. The electrolyte according to claim 8, characterized in that The average particle size of magnesium oxide is in the range of 10 nm to 500 nm; and / or, The average particle size of aluminum oxide ranges from 10 nm to 500 nm.

10. The electrolyte according to claim 8, characterized in that The ratio of the mass of magnesium oxide to the mass of the electrolyte is in the range of 0.001 to 0.05; and / or, The ratio of the mass of aluminum oxide to the mass of the electrolyte is in the range of 0.001 to 0.

05.

11. The electrolyte according to claim 1, characterized in that The electrolyte also includes a dispersant.

12. The electrolyte according to claim 11, characterized in that The dispersant includes: hexadecyltrimethylammonium bromide.

13. The electrolyte according to claim 11, characterized in that The ratio of the mass of the dispersant to the mass of the electrolyte is in the range of 0.005 to 0.

05.

14. The electrolyte according to any one of claims 1 to 13, characterized in that The electrolyte salt comprises: at least one of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide; and / or, The solvent includes at least one of an ether solvent and an ester solvent.

15. A method for preparing an electrolyte, characterized in that: include: calcining the lithium-containing compound; The calcined lithium-containing compound is mixed with an electrolyte salt and a solvent; wherein the lithium-containing compound is in a nanoparticle form.

16. The method for preparing an electrolyte according to claim 15, characterized in that: The calcination temperature ranges from 300°C to 500°C.

17. A lithium ion battery, characterized in that: include: A positive electrode, a negative electrode, and an electrolyte according to any one of claims 1 to 14 located between the positive electrode and the negative electrode.